2017
DOI: 10.4209/aaqr.2016.01.0020
|View full text |Cite
|
Sign up to set email alerts
|

The Concentrations, Formations, Relationships and Modeling of Sulfate, Nitrate and Ammonium (SNA) Aerosols over China

Abstract: Sulfate, nitrate and ammonium (SNA) are the dominant composition of secondary aerosols in the atmosphere and have a significant impact on public health, atmospheric chemistry process and climate. In this study, to evaluate SNA pollution in China, a first nationwide investigation derived from almost all published data in the field measurement before 2012 was carried out. The results show that SNA levels in China are about 3-5 times higher than those in USA and Europe. SNA account for 34.2 ± 10.9% in PM 2.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…The total oxidant O x (O x = O 3 + NO 2 ) was used to characterize the atmospheric oxidation capacity, following Wang et al [14], Jia et al [22], and Clapp and Jenkin [54]. The sulfur oxidation ratio, SOR = n-SO 4 2− /(n-SO 4 2− + n-SO 2 ), was a measure of the conversion degree of sulfur; the nitrogen oxidation ratio, which was defined as NOR = n-NO 3 − /(n-NO 3 − + n-NO 2 ), was used to quantitatively express the conversion degree of nitrogen [55][56][57][58]. was used to quantitatively express the conversion degree of nitrogen [55][56][57][58].…”
Section: High O 3 Concentration and Active Photochemical Activity Promentioning
confidence: 99%
See 1 more Smart Citation
“…The total oxidant O x (O x = O 3 + NO 2 ) was used to characterize the atmospheric oxidation capacity, following Wang et al [14], Jia et al [22], and Clapp and Jenkin [54]. The sulfur oxidation ratio, SOR = n-SO 4 2− /(n-SO 4 2− + n-SO 2 ), was a measure of the conversion degree of sulfur; the nitrogen oxidation ratio, which was defined as NOR = n-NO 3 − /(n-NO 3 − + n-NO 2 ), was used to quantitatively express the conversion degree of nitrogen [55][56][57][58]. was used to quantitatively express the conversion degree of nitrogen [55][56][57][58].…”
Section: High O 3 Concentration and Active Photochemical Activity Promentioning
confidence: 99%
“…The sulfur oxidation ratio, SOR = n-SO 4 2− /(n-SO 4 2− + n-SO 2 ), was a measure of the conversion degree of sulfur; the nitrogen oxidation ratio, which was defined as NOR = n-NO 3 − /(n-NO 3 − + n-NO 2 ), was used to quantitatively express the conversion degree of nitrogen [55][56][57][58]. was used to quantitatively express the conversion degree of nitrogen [55][56][57][58]. The secondary inorganic particulate was defined as SNA = SO4 2-+ NO3 -+ NH4 + .…”
Section: High O 3 Concentration and Active Photochemical Activity Promentioning
confidence: 99%
“…3 , which are formed from SO 2 and NO x (Chang, 1989;McMurry et al, 1983). In addition, NH 3 influences the rate of particle nucleation (Ball et al, 1999;Kulmala et al, 2002) and enhances secondary organic aerosol (SOA) yield (Babar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ions was calculated as the difference between the sums of cations and anions equivalents. In aerosol chemistry, the ammonium plays a significant role in chemical processes, including the formation of secondary ammonium sulfate and ammonium nitrate fine inorganic aerosols [57]. However, previous studies on the chemical composition of snow in Moscow showed that the ammonium in urban snow is about 5%-eq.…”
mentioning
confidence: 98%